Surgical treatment of sphenoorbital meningiomas. Issue 7 (17th January 2011) - Saeed, Peerooz; van Furth, Wouter R; Tanck, Michael; Freling, Nicole; van der Sprenkel, Jan Willem Berkelbach; Stalpers, Lukas J A; van Overbeeke, Jacobus J; Mourits, Maarten P
Abstract : Aim: To evaluate the outcome of surgery and radiotherapy in the treatment of sphenoorbital meningioma (SOM). Method: A retrospective study of 66 consecutive cases treated with surgery for SOM with a minimum follow-up of 4 years. Clinical and radiological information were compared before and after the following surgical approaches: frontotemporal craniotomy, frontotemporal craniotomy combined with orbitozygomatic resection and extended lateral orbitotomy alone. Results: The median age at presentation was 46 years (range, 26–68 years) and the median follow-up after surgery was 102 months (range, 48–288 months). In total, 48 (73%) patients showed preoperative visual deterioration, with visual field defects. All patients had proptosis at presentation (mean±SD=6.4±3.0 mm). Surgery for patients with SOM arrested visual deterioration in 61% and improved vision in 30% of cases. Furthermore, a substantial reduction of proptosis was achieved in 85% of patients. The proptosis in this group was reduced by 2.6±2.6 mm. There was no correlation between surgical approach and proptosis reduction (p=0.125). The recurrence rate was 17%. Only 1 out of 15 patients who underwent radiotherapy showed signs of recurrence. Conclusions: The surgical aims in the treatment of SOM should be the restoration of visual acuity and reduction of proptosis, rather than complete tumour removal. The surgical approach can be tailored to individual cases. The authors recommend radiotherapy in cases of subtotally removed SOM.